Analisis Ekonomi Politik Media Televisi (Studi Tentang Komodifikasi Creative di ANTV) - Rifka Hanifah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
As the Indonesian television industry continues to develop, it requires many media workers to produce programs that are liked by viewers, which enables them to get high ratings and shares. One of these media workers is the creative workers. These individuals often face demanding routines and workloads that do not align with their job descriptions. Additionally, they also have to face the risk of layoffs that rampantly hit major media in Indonesia, including on ANTV. This condition indicates the existence of commodification practices carried out by the media organization. In the commodification practices by Vincent Mosco, it is stated that media workers tend to receive low wages compared to their workload. Therefore, this study aims to explain how creative workers are commodified as media workers at the ANTV. To conduct the research, qualitative methods and a case study approach are used. As for the collection of research data, it was carried out through interviews, observations, and documentation. The findings reveal that commodification practices had occurred at the ANTV but were not noticed by the creative. Furthermore, creative workers are often required to complete multiple tasks outside of their job scope, despite receiving inadequate wages.